Implementasi permenkes 88 tahun 2014 di pukesmas daerah istimewa yogyakarta (DIY) - Tri Hapsari Listyaningrum (JHeS (Journal of Health Studies), 2019)
The provisions of Minister of Health Regulation 88 of 2014 concerning blood tablet supplementary standards for women of childbearing age and pregnant women. The research objective was to determine the implementation of legal products in the community about giving fe tablets to pregnant women in DIY. The research method is juridical sociological, analytic descriptive specifications. The population is 121 health centers in DIY with a purposive sample of 9 health centers, research subjects in the KIA midwife. The results of fe tablet SOP in 4 Puskesmas are Nanggulan, Gamping 2, Sleman and Ngaglik 1. Aspects of failure: packaging of Fe tablets is easily damaged, social, economic and public awareness is lacking. Aspects of success: nutritional counseling, integrated ANC, pregnant women class, husband, in-laws.